Neuronal networks in epileptic encephalopathies with CSWS. (15th June 2016) - Japaridze, Natia; Muthuraman, Muthuraman; Dierck, Carina; von Spiczak, Sarah; Boor, Rainer; Mideksa, Kidist G.; Anwar, Rauf A.; Deuschl, Günther; Stephani, Ulrich; Siniatchkin, Michael
Summary: Objective: The aim of our study was to investigate the neuronal networks underlying background oscillations of epileptic encephalopathy with continuous spikes and waves during slow sleep (CSWS). Methods: Sleep electroencephalography (EEG) studies before and after the treatment were investigated in 15 patients with CSWS. To investigate functional and effective connectivity within the network generating the delta activity in the background sleep EEG, the methods of dynamic imaging of coherent sources (DICS) and renormalized partial directed coherence (RPDC) were applied. Results: Independent of etiology and severity of epilepsy, background EEG pattern in patients with CSWS before treatment is associated with the complex network of coherent sources in medial prefrontal cortex, somatosensory association cortex/posterior cingulate cortex, medial prefrontal cortex, middle temporal gyrus/parahippocampal gyrus/insular cortex, thalamus, and cerebellum. The analysis of information flow within this network revealed that the medial parietal cortex, the precuneus, and the thalamus act as central hubs, driving the information flow to other areas, especially to the temporal and frontal cortex. The described CSWS‐specific pattern was no longer observed in patients with normalized sleep EEG. In addition, frequency of spiking showed a strong linear correlations with absolute source power, source coherence strength, and source RPDC strength at both time points: (1) Spike and wave index (SWI) versus absolute source power at EEG1 (r = 0.56; p = 0.008) and at EEG2 (r = 0.45; p = 0.009); (2) SWI versus source coherence strength at EEG1 (r = 0.71; p = 0.005) and at EEG2 (r = 0.52; p = 0.006); and (3) SWI versus source RPDC strength at EEG1 (r = 0.65; p = 0.003) and at EEG2 (r = 0.47; p = 0.009). Significance: The leading role of the precuneus and thalamus in the hierarchical organization of the network underlying the background EEG points toward the significance of fluctuations of vigilance in the generation of CSWS. This hierarchical network organization appears to be specific for CSWS as it is resolved after successful treatment.